Assessing Interactions among Education, Social Insurance, and Labor Market Policies in a General Equilibrium Framework : An Application to Morocco - Marouani, Mohamed A.; Robalino, David A. (World Bank, Washington, DC, 2012)
This paper develops a general equilibrium model to analyze the marginal and joint impacts that alternative macroeconomic, education, and social protection policies have on the dynamics of employment and unemployment by skill level. The model introduces a disaggregated treatment of the labor market that incorporates an informal sub-sector in every sector of the economy. The analysis explicitly models the distribution of skills in the labor force by following over time sex-age cohorts across various levels of the education system and in the labor market. And it integrates a module that projects the revenues and expenditures of the pension system. The model is applied to the case of Morocco. Simulations show that even under positive assumptions regarding economic growth, unemployment rates are likely to remain close to current levels in the next decade. The paper argues that only an integrated package of policies that affect the macro-economy, the investment climate, and the education and social protection systems would allow sustainable creation of enough "good quality" jobs.